Reforming taste through Pope’s ‘celebrated moonlight scene’: Southey, Coleridge, and Wordsworth’s ‘A Night-Piece’ - Cox, O (Edinburgh University Press, 2023)
In ‘Essay, Supplementary to the Preface’ (1815), Wordsworth condemned Pope’s ‘celebrated moonlight scene in the Iliad’. Pope’s ‘passage of descriptive poetry, which at this day finds so many and such ardent admirers’, did not impress Wordsworth, Southey, and Coleridge, all three of whom drew specifically on this verse-paragraph of Pope’s to expose what they perceived to be faulty poetic diction and ‘corrupted’ taste. In the ‘Essay, Supplementary’, Wordsworth argued that a great poet has ‘the task of creating the taste by which he is to be enjoyed’. This essay argues that Southey, Coleridge, and Wordsworth teach poetic taste through their challenge to Pope’s famous nightpiece. In ‘A Night-Piece’ Wordsworth engages intimately with Pope’s diction, form, and imagery in the moonlight scene in order to contest Popean hegemony.